PERANCANGAN PROGRAM PROSES MANUFAKTUR DAN SIMULASI TROUBLESHOOTING UNTUK MATA KULIAH PRAKTIK FLEXIBLE MANUFACTURING SYSTEM DI PRODI TEKNIK MESIN DAN MANUFAKTUR - Rian Rara Ilham Rian; Fajar Aswin; Husman Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Flexible Manufacturing System (FMS) is a manufacturing system that can react flexibly to changes. The FMS equipment in the Mechanical Laboratory of the State Police of Babel is specifically devoted to the practice course of Advanced Manufacturing Technology in the Mechanical and Manufacturing Engineering study program in semester 5 with 2 credits. The current condition is that the existing FMS tools have not been able to contribute optimally in achieving the learning objectives of FMS practice. The purpose of the FMS practice itself is that students are able to operate the FMS device and simulate several variations of the Manufacturing process. Based on the existing problems, a manufacturing process program design and troubleshooting simulation will be carried out for the FMS practice course in the Mechanical and Manufacturing Engineering study program. In this research, the purpose of this research is to design a program for the manufacturing process in the FMS device using a PLC. The results of this study are to find out the process of drilling metal and non-metal workpieces and make a learning manual for troubleshooting the process.